VeCHAT: a proof-of-concept study on screening and managing veterans - Jim Warren; Margot Darragh; Felicity Goodyear-Smith (CSIRO Publishing, 2021)
ABSTRACT INTRODUCTIONNew Zealand veterans may have complex mental and physical complaints related to multiple exposures to war environments. They are entitled to, but often do not, access a range of physical, mental health and social services funded through Veterans' Affairs New Zealand. eCHAT (electronic Case-finding and Help Assessment Tool) is a self-completed electronic holistic screen for substance misuse, problem gambling, anger control, physical inactivity, depression, anxiety, exposure to abuse; and assesses whether help is wanted for identified issues. AIMA proof-of-concept study was conducted to develop a modified version of eCHAT (VeCHAT) with remote functionality for clinical assessment of mental health and lifestyle issues of contemporary veterans, and assesses acceptability by veterans and Veterans' Affairs staff, and feasibility of implementation. METHODSWe used a co-design approach to develop VeCHAT. Veterans' Affairs and service organisations invited veterans to remotely complete VeCHAT and a subsequent short online acceptability survey. Veterans' Affairs medical and case manager staff underwent semi-structured interviews on feasibility and acceptability of VeCHAT use. RESULTSThirty-four veterans completed VeCHAT. The tool proved acceptable to veterans and Veterans' Affairs staff. Key emergent themes related to tool functionality, design, ways and barriers to use, and suggested improvements. Veterans' Affairs staff considered VeCHAT use to be feasible with much potential. DISCUSSIONCapacity of Veterans' Affairs to respond if their engagement with veterans increases and employment of VeCHAT is scaled up, is unknown. Work is needed to assess how introducing VeCHAT as a standard procedure might influence Veterans' Affairs case management processes.